Hypertensive emergency presenting with acute spontaneous subdural hematoma. Issue 1 (January 2019) - Haddadin, Faris; Munoz Estrella, Alba; Herzog, Eyal
Abstract: Hypertensive crisis is a serious medical condition defined as severely elevated blood pressure; typically the systolic blood pressure is above 180 mmHg, and/or the diastolic blood pressure is above 120 mmHg. Hypertensive crises are divided into two categories: hypertensive urgency and hypertensive emergency. Hypertensive urgency is asymptomatic while hypertensive emergency presents with end-organ damage requiring more aggressive blood-pressure lowering. The common presentations for neurological end-organ dysfunction in conjunction with hypertensive emergency include ischemic strokes, intracranial hemorrhage, subarachnoid hemorrhage, head trauma, and hypertensive encephalopathy. The occurrence of acute spontaneous subdural hematoma (SDH) as a neurological end-organ damage complicating hypertensive crisis is rare and should receive tight blood-pressure lowering to prevent further bleeding. We present a case of hypertensive emergency complicated with acute spontaneous SDH. <Learning objective: Acute spontaneous subdural hematoma as a neurological end-organ damage complicating hypertensive crisis is a rare entity. Hypertensive crisis presenting with acute spontaneous subdural hematoma prompts tight blood pressure control in timely manner to prevent permanent neurological sequalae. Rapid and severe elevation in the blood pressure might be a potential etiology of spontaneous bleeding into the subdural space. Further studies are needed to investigate this finding>.